Retinol is involved in the intestinal regeneration and strengthens the intestinal barrier during refeeding in broiler chickens - Wang, Youli; Zhou, Huajin; Chen, Jing; Wu, Yuqin; Guo, Yuming; Wang, Bo; Yuan, Jianmin (Journal of Integrative Agriculture, 2024)
Fasting is typically used before feeding metabolizable energy assessment in broilers. Previous studies have shown that fasting cause atrophy of the intestinal villus. Whether fasting affects intestinal permeability during refeeding by altering barrier function and nutrient absorption is of concern. Here, 23-d-old broilers were randomly assigned to 5 treatments, fasted for 0, 12, 24, 36, and 48 h, respectively, and then refed for 2 d, to study the impact of different duration of fasting on the intestinal regeneration and barrier function during refeeding. Results showed that the intestinal morphology in fasted birds was recovered in 2 d of refeeding at most. As fasting durations increased, enterocytes per intestinal villus were linearly and quadratically increased (both P<0.05), whereas goblet cells per intestinal villus was linearly decreased (both P<0.05). Besides, the mRNA level of lysozyme was linearly decreased as fasting durations increased during refeeding (both P<0.05), while quadratically increased mucin 2 was observed only after 1 d of refeeding (P<0.05). Linear increase effects were observed for claudin 2 and zonula occludens-1 with increased fasting durations after 1 d of refeeding (all P<0.05), and linear and quadratical effects were observed for claudin 2 at 2 d of refeeding (both P<0.05). Besides, we found that intestinal permeability to creatinine, 4 and 70 kD dextran were linearly and quadratically decreased with increased fasting durations at 6 h and 1 d of refeeding (all P<0.05). Furthermore, jejunum proteomic from birds refed for 6 h showed that birds fasted for 36 h showed increased antimicrobial peptides and upregulated retinol metabolism when compared to the nonfasted birds (P<0.05). Further study showed that retinyl ester catabolism was inhibited during fasting and enhanced during refeeding. Results of intestinal organoid culture showed that retinol benefits the cell proliferation and enterocyte differentiation. In conclusion, the intestinal permeability to small and large molecules was decreased during refeeding by strengthening the intestinal barrier function, and the activated retinol metabolism during refeeding is involved in the intestinal regeneration and strengthens the intestinal barrier.